2004
DOI: 10.1266/ggs.79.165
|View full text |Cite
|
Sign up to set email alerts
|

Differential geographic patterns of mitochondrial DNA variation in two sympatric species of Japanese wood mice, Apodemus speciosus and A. argenteus

Abstract: We examined the gene sequences of mitochondrial cytochrome b (cyt b ) in two Japanese wood mouse species, Apodemus speciosus (n = 89) and A. argenteus (n = 46), which are distributed on the four main islands of Japan (Hokkaido, Honshu, Shikoku, and Kyushu) and on the small islands surrounding them. Apodemus speciosus , the larger of the two species, showed substantial genetic variation, with a maximum of 3% sequence divergence, and remarkable phylogenetic subdivision with two major clades. One clade represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…However, the estimated timings of these colonizations are debatable and vary among taxa. Conversely, some mammals such as A. argenteus (Suzuki et al 2004), hares (<20 ka; Nunome et al unpublished data), and voles (Microtus montebelli; Tomida personal communication) showed less mitochondrial sequence divergence. These observations suggest that several opportunities to colonize the island took place, or that artificial introductions were made of some mammal species now on Sado Island.…”
Section: Colonization Of Terrestrial Mammals On Sado Islandmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the estimated timings of these colonizations are debatable and vary among taxa. Conversely, some mammals such as A. argenteus (Suzuki et al 2004), hares (<20 ka; Nunome et al unpublished data), and voles (Microtus montebelli; Tomida personal communication) showed less mitochondrial sequence divergence. These observations suggest that several opportunities to colonize the island took place, or that artificial introductions were made of some mammal species now on Sado Island.…”
Section: Colonization Of Terrestrial Mammals On Sado Islandmentioning
confidence: 99%
“…We determined the Cyt b gene sequences (1,140 bp) using the method described by Suzuki et al (2004). Sequences were resolved on a 3100 Genetic Analyzer (Applied Biosystems) and assembled into a single consensus sequence with the aid of PROSEQ software (Filatov 2002).…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The two species are both distributed widely in Japanese archipelago and often found sympatrically in forest habitat. Based on molecular evidence, the divergence time is estimated around five or six million years ago [18, 22, 23]. The large Japanese wood mouse, A. speciosus , is found throughout the four main islands and their peripheral islands, including Sado Island, the Izu Islands and the Satsunan Islands [23].…”
mentioning
confidence: 99%
“…Other molecular studies have found evidence of genetic subdivision between populations, but genetic divergence was between clades inhabiting northern Japan and southern Japan and Korea. These include taxa as diverse as plants (Senni et al 2005, Ikeda et al 2006, termites (Park et al 2006), and rodents (Iwasa et al 2002, Suzuki et al 2004, Terashima et al 2006. Only two studies provide evidence of deep genetic divergence between Korea and Japan: one study focusing on ßightless carabid beetles (Tominaga et al 2000) and the other study on the chrysomelid beetle Plateumaris shirahatai Kimoto (Sota and Hayashi 2007).…”
mentioning
confidence: 99%